Does cumulative prostate cancer length (CCL) in prostate biopsies improve prediction of clinically insignificant cancer at radical prostatectomy in patients eligible for active surveillance?. (15th December 2014) - Chen, Derrick J.; Falzarano, Sara M.; McKenney, Jesse K.; Przybycin, Chris G.; Reynolds, Jordan P.; Roma, Andres; Jones, J. Stephen; Stephenson, Andrew; Klein, Eric; Magi‐Galluzzi, Cristina
<x xml:space="preserve">Abstract</x> Objectives To evaluate if cumulative prostate cancer length (CCL) on prostate needle biopsy divided by the number of biopsy cores (CCL/core) could improve prediction of insignificant cancer on radical prostatectomy (RP) in patients with prostate cancer eligible for active surveillance (AS). Patients and Methods Patients diagnosed with prostate cancer on extended (≥10 cores) biopsy with an initial prostate‐specific antigen (iPSA) level of <15 ng/mL, clinical stage (cT) ≤ 2a, and highest biopsy Gleason score 3 + 3 = 6 or 3 + 4 = 7 with <3 positive cores who underwent RP were included in the study. The CCL/core and presence of insignificant cancer (organ‐confined, volume <0.5 mL, Gleason score at RP ≤6) were recorded. pT2 prostate cancer with RP Gleason score ≤3 + 4 = 7 and volume <0.5 mL were categorised as low‐tumour‐volume organ‐confined disease (LV‐OCD). Results In all, 221 patients met the inclusion criteria: the mean age was 59 years and the median iPSA level was 4.5 ng/mL. The clinical stage was cT1 in 86% of patients; biopsy Gleason score was 3 + 3 = 6 in 67% (group 1) and 3 + 4 = 7 in 33% of patients (group 2). The maximum percentage of biopsy core involvement was <50 in 85%; the median CCL/core was 0.15 mm. Insignificant cancer was found in 27% and LV‐OCD in 44% of patients. Group 2 was associated with higher number of positive cores, maximum percentage core involvement, total prostate cancer length, and CCL/core. Group 1 was more likely to have insignificant cancer (39%) or LV‐OCD (54%) than group 2 (3% and 23%, respectively). Group 2 had significantly higher RP Gleason score and pathological stage. Univariate analysis of group 1 showed that the iPSA level, maximum percentage core involvement, prostate cancer length, and CCL/core were all significantly associated with insignificant cancer and LV‐OCD. For group 2, the number of positive cores (1 vs 2) was also significantly associated with LV‐OCD. On multivariate logistic regression analysis, maximum percentage core involvement of <50, and number of positive cores (1 vs 2) were independent predictors of insignificant cancer in group 1; biopsy Gleason score, maximum percentage core involvement of <50 and prostate cancer length of <3 mm or CCL/core of <0.2 mm were all independent predictors of LV‐OCD in the whole population. The maximum percentage of core involvement of <50 and prostate cancer length of <3 mm or CCL/core of <0.2 mm were also independent predictors of LV‐OCD in group 1 patients. Conclusion In patients eligible for AS, a CCL/core of <0.20 mm was significantly associated with insignificant cancer and LV‐OCD. However, when parameters of cancer burden were considered, CCL/core did not independently add any additional value for predicting insignificant cancer in patients with biopsy Gleason score 6. The CCL/core was an independent predictor of LV‐OCD in the whole population and in group 1 patients, although the model including prostate cancer length showed slightly higher area under the receiver operating characteristic curve.